Field Study of Installation Damage for Geosynthetic Clay Liners. Issue 5 (1998) - Fox, P.J.; Triplett, E.J.; Kim, R.H.; Olsta, J.T.
Abstract : Field tests were conducted to assess installation damage for an adhesive-bonded, and a needle-punched, geosynthetic clay liner (GCL). GCL panels were laid on a prepared subgrade and covered to varying thicknesses with clean angular sand and clean angular gravel. After hydration, bulldozers were driven over the test plots. GCL samples were then carefully exhumed and laboratory tests were performed to assess damage according to product type, cover soil type, cover soil thickness, bulldozer type, and number of bulldozer passes after hydration. Visual observations and laboratory test results indicated that the products generally performed well during installation. Damage to the geosynthetic components of the GCLs was minor for a cover soil thickness of 305 mm or greater. Mass per unit area measurements indicated that bentonite migration was insignificant for nearly all specimens; the only exception was the adhesive-bonded GCL covered with gravel and subjected to 10 passes of a medium-weight bulldozer after hydration. No failures were observed for installation conditions that met the guidelines of ASTM D 6102 and the manufacturer. Compared to similar investigations for other geosynthetic materials, installation damage studies for GCLs are unique because of the sensitivity of these products to hydration and overburden stress conditions and the need to quantify bentonite migration due to stress concentrations.